1995
DOI: 10.2136/sssaj1995.03615995005900060028x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Salinity and Sodicity on Soil Structural and Hydraulic Characteristics

Abstract: An exchangeable sodium percentage (ESP) >15 is traditionally considered to affect soil structural and hydraulic characteristics. Recent investigations show that both this critical value and the concept of critical threshold need reconsideration, because soil degradation often takes place even at lower ESP in dilute solutions, and soil behavior at increasing ESP appears to be a continuum. This study was carried out to analyze the response of two Sicilian Typic Haploxererts to ESP values up to 15, at a low ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
38
0
6

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 7 publications
7
38
0
6
Order By: Relevance
“…In the present study, statistical analysis also showed a significant negative correlation between soil ESP values and soil aggregate stability percentage in topsoil ( < 0.01) (Figure 6(d)). The similar negative effects of ESP on soil aggregation were found by other studies [45][46][47]. This might be attributed to that sodium causes swelling and dispersion of soil mineral particles and slaking of unstable aggregates [45,48].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, statistical analysis also showed a significant negative correlation between soil ESP values and soil aggregate stability percentage in topsoil ( < 0.01) (Figure 6(d)). The similar negative effects of ESP on soil aggregation were found by other studies [45][46][47]. This might be attributed to that sodium causes swelling and dispersion of soil mineral particles and slaking of unstable aggregates [45,48].…”
Section: Discussionsupporting
confidence: 83%
“…The similar negative effects of ESP on soil aggregation were found by other studies [45][46][47]. This might be attributed to that sodium causes swelling and dispersion of soil mineral particles and slaking of unstable aggregates [45,48]. In addition, high ESP value can reduce microbial biomass and activity, which may also contribute to the decrease in aggregation [49].…”
Section: Discussionsupporting
confidence: 76%
“…This can in turn decrease soil hydraulic conductivity through the reduction of soil structure and the plugging of soil pores by dispersed clay particles (Abu-Sharar et al, 1987;Yousaf et al, 1987;So and Aylmore, 1993). The slaking-dispersion process can be greatly enhanced when the cationic concentration of the antecedent soil pore water is diluted by infiltrating rainfall and/or low-sodium irrigation water (Frenkel et al, 1978;Crescimanno et al, 1995). In addition, sodium-induced slaking and clay dispersion can be particularly destructive at the soil surface as it may cause the formation of a virtually impermeable surface crust that both impedes water entry into the soil (Agassi et al, 1985;Shainberg et al, 1992) and impairs seedling emergence (Hausenbuiller, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Salt-affected lands can be effectively used and ameliorated through judicious use of various plant species (Chaudhry et al 1985;Robbins 1986;Chang et al 1994;Crescimanno et al 1995). The amounts of Cl Ϫ , SO 4 2Ϫ and HCO 3 Ϫ in soil solution also decreased exponentially as a result of kallar grass growth.…”
mentioning
confidence: 99%